2003
DOI: 10.1161/01.atv.0000051405.68811.4d
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Chymase Induces Smooth Muscle Cell Apoptosis by a Mechanism Involving Fibronectin Degradation and Disruption of Focal Adhesions

Abstract: Objective-Chymase released from activated mast cells has been shown to induce apoptosis of vascular smooth muscle cells (SMCs) in vitro. The proteolytic activity of chymase is essential for the proapoptotic effect, but the mechanism of chymase-induced apoptosis has remained unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 53 publications
4
92
0
Order By: Relevance
“…This procedure allows identification of the initial state of cell activation before irreversible cell damage occurs, and further explores a more advanced state of cell injury characterized by nuclear and cytoplasmic abnormalities typical of apoptosis. The advantage of the proposed procedure is that early morphological changes (membrane blebbing and vesiculation) can be easily identified before anchorage-dependent survival of cells is compromised [19,32,[39][40][41][42]. In the absence of other morphological or structural modifications, these initial membrane changes indicate a reversible response to stimulation by stressors and can be used as indicators of cell stimulation/suffering.…”
Section: Results-discussionmentioning
confidence: 99%
“…This procedure allows identification of the initial state of cell activation before irreversible cell damage occurs, and further explores a more advanced state of cell injury characterized by nuclear and cytoplasmic abnormalities typical of apoptosis. The advantage of the proposed procedure is that early morphological changes (membrane blebbing and vesiculation) can be easily identified before anchorage-dependent survival of cells is compromised [19,32,[39][40][41][42]. In the absence of other morphological or structural modifications, these initial membrane changes indicate a reversible response to stimulation by stressors and can be used as indicators of cell stimulation/suffering.…”
Section: Results-discussionmentioning
confidence: 99%
“…However, tryptase is involved in tissue fibrosis, and chymase induces apoptosis of cells with relatively low differentiation, including vascular smooth muscle cells, bronchial smooth muscle cells, and cardiomyocytes [16][17][18][19][20]. In other words, if we presume that there are undifferentiated cells in the fovea, then with regard to the action of these serine proteases, idiopathic epiretinal membranes may develop when tryptase activity is predominant, and idiopathic macular holes may develop when chymase activity is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lazaar et al (39) previously showed that chymase reduces epidermal growth factor-induced proliferation of SMCs. An alternative explanation for how mMCP-4 may control SMC responses would be that the fibronectin fragments generated in the presence of mMCP-4 could be proapoptotic for SMCs (33), thus possibly preventing an exaggerated SMC expansion in response to OVA treatment. However, numerous other potential targets for chymase have been described, many of which could directly or indirectly affect SMCs and AHR, e.g., substance P, vasoactive intestinal peptide, endothelin-1, angiotensin I, IL-13, and C3a (3).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential substrate for mMCP-4 could be fibronectin. Fibronectin has previously been shown to be a substrate both for human chymase and for mMCP-4 (31, 32) and, considering that proteolytic fibronectin fragments can be proapoptotic for SMCs (33), it was relevant to examine whether fibronectin is differentially processed in lungs from WT and mMCP-4 Ϫ/Ϫ animals. As shown in Fig.…”
Section: Degradation Of Smc Mitogens and Fibronectin By Mmcp-4mentioning
confidence: 99%